LEGAL PROTECTION FOR PARTIES THAT MAKE BINDING AGREEMENTS FOR THE SALE AND PURCHASE OF LAND THAT HAS NOT BEEN CERTIFIED IN THE RESOLVING LAND PARCELS PROCESS - Heriyanti Heriyanti (UNISSULA, 2019)
Land purchase binding agreement in practice is often made in the form of an authentic deed before a Notary, so that the Deed of Sale and Purchase Agreement is an authentic act that has the strength of evidence is perfect. It is intended by the parties to further provide protection and legal certainty for the parties to make. Because notaries in making an act impartially and safeguard the interests of the parties objectively. With the help of the notary of the parties make binding sale and purchase agreement will get help in formulating the things that will be agreed upon. The method used in this research is normative juridical approach to literature. Legal protection of the fulfillment of the rights of the parties where one party is in default under the agreement binding sale and purchase is dependent upon the strength of the agreement binding sale and purchase is made, that if made by deed under the hands of the protection in accordance with the protection of the deed under the hand, whereas if it is made by or in the presence of a Notary, the account will automatically become a notary deed so that the protection is in accordance with the power of protection against authentic deeds.